E-learning Media for the Ability to Recognize and Count Numbers in Kindergarten Students - Fikri Andika Putra Mulyana; Asep Bayu Dani Nandiyanto; Tedi Kurniawan (Universitas Komputer Indonesia, 2022)
The Covid-19 pandemic causes learning activities to be carried out online, causing teachers to be able to utilize technology-based learning media. This study aims to determine whether there is a significant difference between the ability to work on kindergarten students' numeracy questions before and after being given learning through YouTube media. The method that will be used is descriptive quantitative to 19 kindergarten students. The results show that the data processing of the Wilcoxon test results is 0.449>α=0.05. From these results, we can conclude that the YouTube learning media has no significant effect on the ability to recognize numbers and do arithmetic problems. This is because (i) the research time is short, (ii) the instructional video is only given once, (iii) some parents do not provide learning videos to students, and (iv) there are still many students who have difficulty writing numbers correctly. But of course, the experience of students learning to use YouTube can still be useful to help students continue their education to the next level.